A study the factors that influence perceptions of work-life balance in public sector / Nur Hakimah Mohd Noor - Mohd Noor, Nur Hakimah (2015)
The objective of this study is to investigate the factors that influence perceptions of work-life balance among employee in Universiti Teknologi MARA, Perlis. The population on this study was 401 lecturers. Based on the population number which was 401 lecturers but only 210 lecturers had been selected as the sample size. The result revealed that there was a positive relationship which are work-life conflict, job involvement, and spouse support. There was also a negative relationship which was job involvement with work-life balance. In order due to some of the hypothesis were accepted here had some recommendation could be suggested. As the examples, employee should manage their time effectively to make it balance, create more awareness and knowledge among employee concerning of flexible working, must open about your need in your work and have reliability to manage various roles.